Elevated plasma interleukin-6 levels in trained male triathletes following an acute period of intense interval training - Robson-Ansley, P. J.; Blannin, A.; Gleeson, M (European Journal of Applied Physiology, 2007)
The aim of the present study was to investigate possible changes in the plasma IL-6 levels, subjective reporting of sources and symptoms of stress and the innate immune system in response to an acute period of intensified run training in highly trained endurance athletes. Eight healthy endurance trained male subjects (mean ± SD age 23 ± 2 years, VO2max 64.8 ± 2.6 ml kg-1 min-1, mass 77.1 ± 2.9 kg) completed the study which took place over a 4 week period. In weeks 2 and 3, in addition to their normal endurance training, subjects completed interval-training run sessions on three successive days. Saliva and venous blood samples were taken at the end of each week. Blood samples were analysed for leukocyte counts; neutrophil function; plasma IL-6; creatine kinase activity; and cortisol. Symptoms and sources of stress were assessed by questionnaire. Plasma IL-6 and creatine kinase activity were elevated following intensified training. Neutrophil function was reduced but total leukocyte and neutrophil counts, plasma cortisol and salivary IgA remained unchanged. There was a worsening in symptoms of stress despite there being no significant change in the sources of stress during intensified training. In conclusion, an acute period of intensified training can induce a suppression of the innate immune system and a chronic elevation in IL-6. This was associated with an increase in fatigue and generalised malaise which lends support to the recent cytokine theories of unexplained, underperformance syndrome.